SISTEM PENGELOLAAN PENGADUAN DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA PDAM TIRTA KAHURIPAN KABUPATEN BOGOR - Wulandari, Yuni; Hernawan, Denny; Purnamasari, Irma (JURNAL GOVERNANSI, 2016)
Regional Water Company (PDAM) is a company that is managed by the Local Government to operate as a body of community service that is selling services and trust in society. PDAM has to must still understand the behavior and wishes of the customers in the utilization of services of drinking water and the discretion of the company in the form term of service standards set, so as to provide a good service that causes customers to be satisfied.                One of the PDAM in Indonesia is PDAM Tirta Kahuripan located in Bogor. PDAM Tirta Kahuripan is often get complaints from their customers. Of the Many customers who complained about the poor service system so far is are leaky pipe impact on the high notes of erroneous meter, water quality is still dirty muddy, and sluggish handling of a complaint.                The aim of research is to find out a complaint management system in order to improve customer satisfaction at PDAM Tirta Kahuripan.               The theory used to analyze a system of customer complaints is the referring to the Minister of Administrative Reform and Bureaucratic Reform No. 3 Year of 2015 on the Road Map Development Complaints Public Service Nationwide with 3 sizes of complaint management : outcomes, targets, and programs. While, improving customer satisfaction using Fandi Tjiptono and Gregory Cahndra theory (2006: 130) with four dimensions to measure customer satisfaction : the system of complaints and suggestions, Customer satisfaction Survey, Ghost Shopping (Shadow Customer), and Customer Switching Analysis.               Research methods used in this research is descriptive quantitative method using questionnaires / questionnaire and interviews as the main instrument to collect data.                The results showed that the management of customer complaints in accordance with  to existing procedures with the acquisition of a score of is 3.32 according to the with category of interpretation of the category is as quite good enough (moderate).  Meanwhile, the results of data analysis by increasing customer satisfaction PDAM Tirta Kahuripan obtained a score of is 2.83 in the category with category of interpretation as good enough (moderate).                  Nevertheless, But there is a needs to be have a system or application that can be accessed in to the customer complaints and the organizers therefore PDAM can respond and follow complaint subsequently. Keywords : Complaint Management System , Customer Satisfaction